Reproductive management: conditioning, spawning and development of Peruvian grunt Anisotremus scapularis in southern Peru - Renzo Pepe-Victoriano; Jordan I. Huanacuni; Pablo Presa; Luis Antonio Espinoza-Ramos (PeerJ)
The Peruvian grunt, Anisotremus scapularis, is beginning its domestication as a candidate species for marine aquaculture. The optimal management of fingerling production requires precise knowledge on early development. Herein, we report the methodology for capturing and conditioning wild specimens to find a viable broodstock. The speed of capture and transportation (about 30 min), the post capture preventive treatment (60 min with tetracycline), and the 6-days preventive antiparasitic treatment (29 ppm formalin) maximized survival and a rapid feeding adaptation. Progressive diets based on the copepod Emerita analoga, fish meal, pellets and processed feedstuff prompted the spontaneous broodstock spawning 7 months post-capture. The interannual spawning of this broodstock since September 2016 indicated the optimal control of its reproduction in captivity. The morphogenetic process of the embryo lasted 42 h at 18 °C compared to (31–41) h at 19 °C in northern Peruvian latitudes. The knowledge generated allowed us to work out broodstock and egg management protocols in southern Pacific latitudes (southern Peru and northern Chile). Such protocols would help to escalate larval and juvenile production and to alleviate fishing pressure on the overexploited Peruvian grunt population.